PENGUNGKAPAN TANGGUNG JAWAB SOSIAL DAN KARAKTERISTIK CORPORATE GOVERNANCE PADA SEKTOR FINANSIAL - Wardhani, Saskiya Rahma; Cahyonowati, Nur (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2011)
The aim of this research is to examine the relation of corporate governance and corporate socialresponsibility disclosure on public companies listed at the Jakarta Stock Exchange. Disclosureof corporate social responsibility was measured by using modified Hackton and Milne’s(1996) indicators. This research predicts that corporate social disclosure is determined by thecharacteristics of corporate governance i.e. size of the board of commissioners; independentcommissioners, independent audit committees, government ownership, and presence of womenthe board of commissioners. Company size and profitability is used as control variables. Thissample consists of companies in financial sector. There are 45 companies fulfilling the samplingcriterion. The data were then analyzed using multiple regression analysis. The results indicatedthat the size of the board of commissioners, government ownership, independent audit committee,and company size had a positive and significant relation on the disclosure of corporate socialresponsibility; but the independent commissioners, the presence of women in the board ofcommissioners, and profitability did not have a significant relationship.